1994
DOI: 10.1007/bf00868249
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course of hepatitis B virus-associated nephropathy

Abstract: Hepatitis B virus (HBV) infection is recognised as an important cause of nephrotic syndrome in endemic areas. This paper retrospectively examines the natural history and treatment of 70 patients with membranous glomerulonephritis and 1 with mesangiocapillary glomerulonephritis associated with HBV infection. Thirty-seven patients were in complete remission by the end of the study. The average duration of proteinuria in these patients was 30 months. The cumulative probability of remission was 64% at 4 years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 18 publications
3
35
1
1
Order By: Relevance
“…The diagnosis is based on an assessment of the status of HBV replication (HBeAg/Ab and HBV DNA levels) [126] , laboratory findings (urinalysis and liver function test) and a kidney biopsy, although it is sometimes difficult to detect the deposition of viral antigens in the kidney by routine immunohistochemical analysis. HBV-associated nephrotic syndrome due to membranous nephropathy is not uncommon in children, and spontaneous recovery has been reported, which is often associated with seroconversion of HBeAg to anti-HBe [127] . In adults, on the other hand, spontaneous resolution is relatively uncommon and antiviral therapy may be effective [128] .…”
Section: Renal Diseases Associated With Liver Diseasesmentioning
confidence: 99%
“…The diagnosis is based on an assessment of the status of HBV replication (HBeAg/Ab and HBV DNA levels) [126] , laboratory findings (urinalysis and liver function test) and a kidney biopsy, although it is sometimes difficult to detect the deposition of viral antigens in the kidney by routine immunohistochemical analysis. HBV-associated nephrotic syndrome due to membranous nephropathy is not uncommon in children, and spontaneous recovery has been reported, which is often associated with seroconversion of HBeAg to anti-HBe [127] . In adults, on the other hand, spontaneous resolution is relatively uncommon and antiviral therapy may be effective [128] .…”
Section: Renal Diseases Associated With Liver Diseasesmentioning
confidence: 99%
“…Brzosko et al [53]first described this pathological entity, and subsequent reports from other countries showed that the strongest association of chronic HBV carriage, particularly in children, is with MN [1, 7, 31, 33, 34, 35, 36, 37, 38, 39]. In children, HBV-associated membranous nephropathy (HBVMN) resolves spontaneously in many cases, usually in association with the appearance of free anti-HBeAb in the circulation [40, 41].…”
Section: Pathology Of Hbv-associated Glomerulonephritismentioning
confidence: 99%
“…The majority of children however have a benign course. A report by Gilbert and Wiggelinkhuizen [31]in 1994 in a study from Cape Town reported 71 children with HBV-associated nephropathy. In this cohort of patients, 37 (52.1%) of patients went into spontaneous remission, this was associated with HBeAg clearance in 33 patients (89.2%) over 90 months; the average time of clearance of HBeAg to remission was 5 months.…”
Section: Clinical Course and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between chronic HBV infection and glomerulonephritis is confirmed, which draws an increasing attention due to widespread infection of HBV in Chinese children. Most patients with HBV-GN present with nephrotic syndrome, and some of them show refractory proteinuria and eventually progress to end-stage renal failure [2,3]. Membranous nephropathy is the predominant pathological type of HBV-GN in children.…”
Section: Introductionmentioning
confidence: 99%